Influence of Environmental Regulation on Corporate Green Supply Chain Management: The Regulating Effect of Environmental Dynamism - Wang, Songlin; Zhang, Xuan (Frontiers in Environmental Science, 2022)
Environmental pollution, resource waste, and ecological imbalance have raised global concerns. Against this backdrop, green supply chain management (GSCM) becomes the focus of corporate sustainable development. Based on the institutional theory, thus study explores the influence of command-and-control environmental regulation (CCER) and market-based environmental regulation (MBER) over GSCM, as well as the regulating effect of environmental dynamism on the influence. A total of 191 valid responses were obtained through a questionnaire survey. The analysis of these responses shows that: CCER and MBER positive affect GSCM; environmental dynamism negatively regulates the correlations of CCER and MBER with GSCM. Based on these findings, theoretical guides and managerial implications were obtained for corporate GSCM.